Withholding homicide victim names: Looking for a win-win solution for families and the police - Rick Ruddell; Jody Burnett (Journal of Community Safety and Well-Being, 2019)
Although withholding the names of homicide victims from the public is a relatively new police practice, it has proven to be controversial, with the media, legal scholars, and victim advocacy groups often opposing these policies. In order to better understand the issue of withholding names, we examined the prevalence of these practices in Canada’s largest municipal police services. These results were further explored in a series of semi-structured interviews with stakeholders from 20 victim services and advocacy organizations. Analysis of the interview and survey results reveal that the key priority of the police is maintaining the integrity of their investigations, and all other issues are secondary. Although the issue of withholding information has become contentious, many of the arguments become moot, as the friends and family members of these victims often post the information related to these deaths on social media, effectively bypassing both the press and the police. Implications for policy development are discussed in light of these findings.